Preventing domestic abuse for children and young people: A review of school-based interventions. (December 2015) - Stanley, Nicky; Ellis, Jane; Farrelly, Nicola; Hollinghurst, Sandra; Downe, Soo
Abstract: Schools provide the setting in which interventions aimed at preventing intimate partner violence and abuse (IPVA) are delivered to young people in the general population and a range of programmes have been designed and evaluated. To date, most rigorous studies have been undertaken in North America and the extent to which programmes are transferable to other settings and cultures is uncertain. This paper reports on a mixed methods review, aimed at informing UK practise and policy, which included a systematic review of the international literature, a review of the UK grey literature and consultation with young people as well as experts to address the question of what works for whom in what circumstances. The context in which an intervention was delivered was found to be crucial. Context included: the wider policy setting; the national or regional level, where the local culture shaped understandings of IPVA, and the readiness of an individual school. The programmes included in the systematic review provided stronger evidence for changing knowledge and attitudes than for behavioural change and those young people who were at higher risk at baseline may have exerted a strong influence on study outcomes. Shifting social norms in the peer group emerged as a key mechanism of change and the young people consulted emphasised the importance of authenticity which could be achieved through the use of drama and which required those delivering programmes to have relevant expertise. While the consultation identified increasing interest in targeting interventions on boys, there was an identified lack of materials designed for minority groups of young people, especially Lesbian, Gay, Bisexual and Transgender young people. Increased responsivity to the local context can be achieved by involving those who will deliver and receive these preventive programmes in their development. Schools need to be better prepared and supported in the task of delivering these interventions and this is particularly relevant for the management of disclosures of IPVA. Outcomes measured by evaluations should include those relevant to education. Highlights: National policy, culture and school readiness form a vital context in IPVA prevention. Programmes transported across cultures should incorporate local values and content. Authenticity emerged as a key ingredient of successful preventive interventions. Those children and young people experiencing IPVA may require additional support.